Loss of MAR1 Function is a Marker for Co-Selection of CRISPR-Induced Mutations in Plants - Rinne, Jannis; Witte, Claus-Peter; Herde, Marco (Frontiers in Genome Editing, 2021)
In this study, we describe the establishment of the knockout marker gene MAR1 for selection of CRISPR/Cas9-edited Arabidopsis seedlings and tomato explants in tissue culture. MAR1 encodes a transporter that is located in mitochondria and chloroplasts and is involved in iron homeostasis. It also opportunistically transports aminoglycoside antibiotics into these organelles and defects of the gene render plants insensitive to those compounds. Here, we show that mutations of MAR1 induced by the CRISPR system confer kanamycin-resistance to Arabidopsis plants and tomato tissues. MAR1 is single-copy in a variety of plant species and the corresponding proteins form a distinct phylogenetic clade allowing easy identification of MAR1 orthologs in different plants. We demonstrate that in multiplexing approaches, where Arabidopsis seedlings were selected via a CRISPR/Cas9-induced kanamycin resistance mediated by MAR1 mutation, a mutation in a second target gene was observed with higher frequency than in a control population only selected for the presence of the transgene. This so called co-selection has not been shown before to occur in plants. The technique can be employed to select for edited plants, which might be particularly useful if editing events are rare.